(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
Education plays a significant role in life for the reason that it is a key determinant of personal well-being and welfare. Educated people live fuller and happier lives, have more employment options and are rewarded with higher salary. Consequently, education boosts their independence and allows to be positive members of society. Children with disabilities need education in order to develop understanding of the world, join the employment market, make the right decisions and establish their independence. Teachers also play a very critical role in the proper education of children with special educational needs. Being a teacher of exceptional students requires a number of personality traits such as patience, composure and sensibility. It is important to build collaborative partnerships between teachers, students their parents and the supporting team of psychologists and therapists. The a rticle i s a n a ttempt t o a nalyse a complex role of the teacher of children with disabilities and education.